1977
DOI: 10.1037/0022-3514.35.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Toward an understanding of crowding: The role of physical interaction.

Abstract: It was hypothesized that the widespread failure of crowding studies to show decrements in task performance as a function of density was due to the omission of physical interaction from laboratory analogues of crowding Using male subjects, the present study manipulated density (high vs. low) and physical interaction (high vs. low) in a 2 X 2 design. It was found that decrements in performance on cognitive and behavioral components of the experimental task occurred only in the high density -high physical interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 22 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…Although Heller et al's (1977) as well as Langer and Saegert's (1977) findings are compatible with our assumption that social interference has adverse effects on self-control, they do not constitute sufficient evidence. Because the tasks were performed during the experience of social interference in supposedly highly sensory-demanding environments, increased cognitive load rather than reduced self-control strength might have impaired performance in these tasks.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…Although Heller et al's (1977) as well as Langer and Saegert's (1977) findings are compatible with our assumption that social interference has adverse effects on self-control, they do not constitute sufficient evidence. Because the tasks were performed during the experience of social interference in supposedly highly sensory-demanding environments, increased cognitive load rather than reduced self-control strength might have impaired performance in these tasks.…”
Section: Introductionsupporting
confidence: 70%
“…Since social interference has been argued to be central in crowding (Schopler & Stockdale, 1977), the present findings suggest that it may be worthwhile to investigate self-control processes further, as an explanation of observed effects of crowding. As we have already mentioned in the introduction, Heller et al's (1977) as well as Langer and Saegert's (1977) findings on reduced task performance in crowded situations may, at least in part, be determined by diminished selfcontrol strength stemming from exposure to social interference. Further evidence that effects of crowding may be attributed to reduced self-control strength comes from studies on helping behaviour: A recent study that was theoretically based on the strength model of self-control demonstrated that initial depletion of self-control strength subsequently decreased participants' willingness to help others (DeWall, Baumeister, Gailliot, & Maner, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations